THE USAGE OF MODERN PEDAGOGICAL TECHNOLOGIES FOR DEVELOPING CRITICAL THINKING (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
This article explores the effective application of modern pedagogical technologies aimed at fostering critical thinking skills among students. It examines innovative teaching methods, digital tools, and interactive strategies that enhance learners’ analytical, evaluative, and problem-solving abilities. The study highlights the integration of critical thinking tasks into curriculum design and demonstrates how technology-supported education contributes to deeper intellectual engagement and independent reasoning.